'When two or three are gathered' in a Zoom Room: The Theology of Online Unprogrammed Quaker Worship. Issue 2 (1st December 2021) - Dandelion, Pink; Grant, Rhiannon
Abstract : This research note uses data from surveys of Quaker Meetings in Britain in 2020 to offer reflections into the theology of online worship. It provides both an overview of the changes Meetings made as a result of the Coronavirus pandemic and a discussion of the nature of online worship, including to what extent 'meeting' online is experienced as 'gathered' or 'worship'. It ends by highlighting the longer-term consequences that may result from the temporary and pragmatic changes Quakers made locally.